2013
DOI: 10.1002/btpr.1736
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid modeling and performance analysis of a bidirectional rotating perfusion culture system

Abstract: A myriad of bioreactor configurations have been investigated as extracorporeal medical support systems for temporary replacement of vital organ functions. In recent years, studies have demonstrated that the rotating bioreactors have the potential to be utilized as bioartificial liver assist devices (BLADs) owing to their advantage of ease of scalability of cell-culture volume. However, the fluid movement in the rotating chamber will expose the suspended cells to unwanted flow structures with abnormally high sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Many of the bioreactor systems are flow-based culture systems, and computational fluid dynamics (CFD) modeling is well suited to optimize bioreactor design as it provides a tool to describe fluid dynamics in the engineered culture devices (Kang et al, 2013 ; Hsu et al, 2014 ). CFD modeling allows parameter values to be varied and the effects on the system to be characterized rapidly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the bioreactor systems are flow-based culture systems, and computational fluid dynamics (CFD) modeling is well suited to optimize bioreactor design as it provides a tool to describe fluid dynamics in the engineered culture devices (Kang et al, 2013 ; Hsu et al, 2014 ). CFD modeling allows parameter values to be varied and the effects on the system to be characterized rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be used to describe spatiotemporal distributions of a test compound or oxygen within the system. CFD and other computational methods have previously been applied to enhance our understanding of system parameters fundamental for cell responses within complex 3D culture environments (Kang et al, 2013 ; Hsu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have shown on their works the benefits of simulations for the design and optimization of bioreactors and other kind of equipment. (Haringa et al, 2018;Kang et al, 2013;Trejo et al, 2012;Moilanen et al, 2006) In this study, the kinetic model developed by Biswas et al (2006) was applied to a tubular reactor using an intermittent feeding method. Additionally, a modification to the original model was proposed to include inhibition of methane production caused by high concentrations of acids in the reactor.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, pressure drop predictions as a function of the scaffold permeability have been demonstrated for scaffolds with a variety of mechanical properties (elastic modulus and Poisson's ratio) to optimize the bioreactor design (Podichetty et al, ). Moreover, advection‐diffusion equations have been coupled with the hydrodynamics and mass transfer equations to increase model complexity and study the dynamic effect of cell colonization on the fluid‐induced stress distribution (Kang et al, ; Pearson et al, ; Spencer et al, ) within a tissue scaffold. Specifically, these reported studies aim to optimize the flow properties and bioreactor geometry to preclude any scaffold deformation or non‐uniform fluid‐induced shear stress distributions due to poroelasic phenomena that yield non‐uniform cell colonization.…”
Section: Introductionmentioning
confidence: 99%